TREATMENT OUTCOMES OF PACLITAXEL–CARBOPLATIN–BEVACIZUMAB FOR RECURRENT OR METASTATIC EPITHELIAL OVARIAN CANCER AT NGHE AN ONCOLOGY HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objectives: Treatment Outcomes of Paclitaxel–Carboplatin–Bevacizumab in Patients with Recurrent or Metastatic Epithelial Ovarian Cancer at Nghe An Oncology Hospital from January 2020 to September 2025.Materials and methods: A retrospective descriptive study was conducted in 30 patients with recurrent or metastatic epithelial ovarian cancer who received the Paclitaxel-Carboplatin-Bevacizumab regimen at Nghe An Oncology Hospital between January 2020 and September 2025. Demographic, clinical, and laboratory data, along with treatment response, survival outcomes, and treatment-related adverse events, were ollected from medical records and analyzed.Results: The mean age of the patients was 54.4 ± 8.78 years, with the 51–70-year age group accounting for the majority (73,3%). High-grade serous carcinoma was the predominant histopathological subtype, representing 76,7% of cases. The disease control rate (DCR) was 86.6%, with 8 patients (26.7%) achieving a complete response (CR) and 14 patients (46.7%) achieving a partial response (PR), resulting in an overall response rate (ORR) of 73.4%.The median progression-free survival (PFS) was 15.25 months and was not significantly associated with age group, performance status, or surgical status at the time of recurrence.Neutropenia was predominantly grade 1–2, while grade 3–4 events were infrequent. The incidence of sensory neuropathy was 53.3%, with grade 3 toxicity observed in only 2 patients (6.7%), and no cases of grade 4 toxicity. Grade 1–2 hypertension occurred in 3 patients, with no cases of grade 3 or higher hypertension. 2 patients (6.7%) experienced Carboplatin-induced anaphylactic shock grade 3 during the 5th treatment cycle and were subsequently switched to Cisplatin instead of Carboplatin desensitization.Conclusions: The paclitaxel–carboplatin–bevacizumab regimen demonstrated favorable efficacy with an acceptable safety profile in patients with recurrent or metastatic epithelial ovarian cancer.
Keywords: Metatatis/recurrent epithelial ovarian cancer, Paclitaxel-Carboplatin-Bevacizumab.